Homo resiliens: moralidades e resistências da velhice mediada por smartphones em São Paulo - Duque, Marília (2021)
This thesis addresses how older adults in Sao Paulo city comply with the call for healthy ageing as proposed by the Active Ageing framework highlighting how smartphone’s adoption influence their practices and decisions. This discussion is placed between two poles. One refers to the strategy (moralities and discourses). The other refers to the tactics (everyday practices). Both are approached with contributions from Communication and Consumption, Ethics and Anthropology fields, which results in a qualitative multi-methodological research. The methodology combines French Discourse Analysis (strategy pole), a 16-months ethnography and in-depth interviews (tactic pole). This research design considered that the strategy pole refers to what older adults should do while the tactics pole refers to what they want to do. Between them, there is also what older adults are able to do as smartphones’ users. This ability is ambivalent as, at the same time, it empowers older adults to do what they are supposed to do and what they want to do. On one hand, smartphones would allow older adults to act as protagonists in the participatory health system stablished by the Telemedicine 2.0. On the other hand, smartphones could expand the space for resistances to the digital sphere, allowing them to keep unhealthy behaviors without compromising their identity as active citizens. This global normative identity (morality) is associated with healthy habits which would be facilitated by the use of smartphones in everyday life (tactics). These habits are experienced in a local context, with its own morality and possibilities. Therefore, there is a negotiation between global and local expectations. In that sense, this thesis argues the Active Ageing framework reinforces the local morality in Sao Paulo, as a city where inactivity is seen as a moral failure. Even so, social networks and WhatsApp groups allow older adults to keep their “irresponsible” unhealthy habits in the shadows without compromising their reputation. However, at the same time smartphones work as alibis, they play a significant role in the health tactics adopted by participants, but with one particularity. The use of m-Health apps or “Doctor Google” are how technology would empower them to manage their health. Instead, as observed, WhatsApp is the app they use every day for health and self-care practices. Reduced to WhatsApp or not, smartphones allow participants to perform resilience, which became an imperative and a virtue in old age. As a consequence, this thesis proposes active older adults are framed as Homo resiliens (resilient men).